Critical observations on and suggested ways forward for healthcare communication during COVID-19: pEACH position paper. Issue 2 (February 2021) - White, Sarah J; Barello, Serena; Cao di San Marco, Eugenia; Colombo, Cinzia; Eeckman, Edgard; Gilligan, Conor; Graffigna, Guendalina; Jirasevijinda, T; Mosconi, Paola; Mullan, Judy; Rehman, Shakaib Ur; Rubinelli, Sara; et al.
Highlights: Communication in healthcare and COVID-19 have a mutually influential relationship that is informed by policy and has influenced practice. The fast-pace at which policies have been developed for and practice has adapted to COVID-19 necessitates critical reflection. Evidence-based guidance for communication in healthcare in COVID-19 is central to shaping approaches to public health communication. Evidence-based guidance is also necessary for the challenges faced in communicating with patients, their families, and carers during COVID-19. Abstract: Objective: Communication in healthcare has influenced and been influenced by the COVID-19 pandemic. In this position paper, we share observations based on the latest available evidence and experiential knowledge that have emerged during the pandemic, with a specific focus on policy and practice. Methods: This is a position paper that presents observations relating to policy and practice in communication in healthcare related to COVID-19. Results: Through our critical observations as experts in the field of healthcare communication, we share our stance how healthcare communication has occured during the pandemic and suggest possible ways of improving policy and professional practice. We make recommendations for policy makers, healthcare providers, and communication experts while also highlighting areas that merit further investigation regarding healthcare communication in times of healthcare crises. Conclusion: We have witnessed an upheaval of healthcare practice and the development of policy on-the-run. To ensure that policy and practice are evidence-based, person-centred, more inclusive and equitable, we advocate for critical reflection on this symbiotic relationship between COVID-19 and the central role of communication in healthcare. Practice implications: This paper provides a summary of the key areas for development in communication in healthcare during COVID-19. It offers recommendations for improvement and a call to review policies and practice to build resilience and inclusive and equitable responsiveness in communication in healthcare.